'If only I were a boy …': Psychotherapeutic Explorations of Transgender in Children and Adolescents. (14th March 2022) - Evans, Marcus
Abstract : This paper is based on the author's experience of working with a particular group of female/male trans children and young people who present a similar clinical profile: a fragile ego prone to fragmentation and concrete thinking. Often, there is evidence of a grievance over the failed ideal object, which is internalized, projected into the body, and then attacked. Faced with the developmental challenge of sexuality at puberty, young adults withdraw to a psychic retreat designed to halt development. This paper focuses on the development of a trans identity in defence against an underlying fear of depressive anxieties and psychic collapse. It describes the ongoing assessment of Joanne, a 19‐year‐old biological female who wanted to be known as Luke in therapy and wished to transition in the belief that this was the only way she could have a life. The concrete nature of Joanne's thinking created problems in the therapy, as thoughts were often experienced as physical actions. This paper describes the function of the phantasy that transitioning performs in creating a psychic retreat from the demands of psychological development.